Pengaruh Model Team Game Tournament (TGT) Terhadap Peningkatan Responsibility siswa dalam Pembelajaran Penjas Kelas VIII SMP Negeri 4 Kota Tasikmalaya - Resty Agustryani; Melya Nur Herliana; Novi Soraya (Universitas PGRI Semarang, 2020)
The Effect of Team Game Tournament (TGT) Model on Increasing Student Responsibility in Physical Education Class VIII Junior High School Public 4 of Tasikmalaya CityThis study aimed to determine the effect of Team Game Tournament (TGT) Cooperative Learning on Increasing Students' Responsibility in physical education learning. The research variables were as follows: 1) TGT and conventional learning methods as the independent variables, 2) eight grade students of SMPN 4 Tsikmalaya as the attribute variable, and 3) increased responsibility as the dependent variable. The results of this study were Mann-Whitney test results obtained in the control group before being given a small ranking treatment that is 90 and a large ranking that is 102, as well as in the small ranking experimental group that is 90 and a large ranking that is 102. Whereas in the control group after being given rank treatment the small one is 90 and the big ranking is 108, and in the experimental group the small ranking is 105 and the big ranking is 120. Conclusion of this study that there is an increase in the questionnaire score of the attitude of responsibility before and after treatment is given. Test the effect of treatment on the value of post responsibility between the control group and the experimental group obtained significant results that there are differences that affect the responsibility of students of SMP N 4 Tasikmalaya City.Keywords: Responsibility, Learning Model, Team Game Tournament (TGT) Penelitian ini bertujuan untuk mengetahui: (1) Pengaruh Model Pembelajaran Kooperatif Tipe Team Game Tournament (TGT) Terhadap Peningkatan Responsibility Siswa dalam Pembelajaran Penjas. Variabel penelitian sebagai berikut: 1) variabel bebas yaitu model pembelajaran Team game tournament dan konvensional. 2) variabel atribut yaitu kelas VIII SMP Negeri 4 Kota Tasikmalaya. 3) variabel terikat: peningkatan responsibility. Hasil penelitian ini adalah Hasil uji test Mann-Whitney didapat pada kelompok control sebelum diberikan perlakuan rangking yang kecil yaitu 90 dan rangking yang besar yaitu 102, serta pada kelompok eksperimen rangking yang kecil yaitu 90 dan rangking yang besar yaitu 102. Sedangkan pada pada kelompok kontrol setelah diberikan perlakuan rangking yang kecil yaitu 90 dan rangking yang besar yaitu 108, serta pada kelompok eksperimen rangking yang kecil yaitu 105 dan rangking yang besar yaitu 120. Kesimpulan dalam peneliain ini bahwa terdapat peningkatan skor angket sikap tanggung jawab sebelum dan setelah diberikan perlakuan. Uji efek perlakuan terhadap nilai sikap tanggung jawab post antara kelompok kontrol dan kelompok eksperimen didapatkan hasil yang signifikansi yaitu terdapat perbedaan sehingga memberikan pengaruh terhadap responsibility siswa SMP N 4 Kota Tasikmalaya.Kata kunci: Responsibility, Model Pembelajaran, Team Game Tournament (TGT)